Speech Acts of Racism in the Comment Column of Rachel Zegler Instagram Account as Snow White - Salsabila Nurhusna; Lili Awaludin; Irman Nurhapitudin (Universitas Pahlawan Tuanku Tambusai, 2026)
Racism remains prevalent on social media, where discriminatory attitudes are frequently expressed through language. This study aims to identify the speech acts used in racist comments on Rachel Zegler’s Instagram account and examine the types of racism they represent. Rachel Zegler’s casting as Snow White generated widespread online controversy because some audiences criticized the casting of a Latina actress in a role traditionally portrayed as a white European princess, prompting intense public debate and numerous racist responses on social media. A qualitative descriptive method with purposive sampling was employed to analyze ten racist comments posted in response to this controversy. The data were interpreted using Searle’s Speech Act Theory and Braveman’s racism framework. The findings identified three categories of speech acts: representative, expressive, and directive, with representative speech acts occurring most frequently. The comments reflected two dominant forms of racism: individual racism, expressed through racial insults and derogatory labeling, and cultural racism, manifested through stereotypes about the representation of Snow White. These findings demonstrate how speech acts function as linguistic strategies for expressing and legitimizing racism in online discourse, contributing to pragmatic and critical discourse studies on digital communication and hate speech.